A textbook of differential equations - Ansari A.A., Srivastava R.J., Dubey S.K.D. & others (Swastik publishers & distributors,Delhi, 2007)
Stats/Maths
ENGLISH
Keywords: A textbook of differential equations; Stats/Maths; Stats/Maths